1999
DOI: 10.1038/sj.cdd.4400497
|View full text |Cite
|
Sign up to set email alerts
|

Purification and catalytic properties of human caspase family members

Abstract: Members of the caspase family of cysteine proteases are known to be key mediators of mammalian inflammation and apoptosis. To better understand the catalytic properties of these enzymes, and to facilitate the identification of selective inhibitors, we have systematically purified and biochemically characterized ten homologues of human origin (caspases 1 ± 10). The method used for production of most of these enzymes involves folding of active enzymes from their constituent subunits which are expressed separatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
140
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(147 citation statements)
references
References 27 publications
7
140
0
Order By: Relevance
“…Caspase-9 cleaves Raf-1 at position D279, which is conserved in human and mouse Raf-1. D279 and its context do not fit the proposed consensus motif for a caspase-9 cleavage site (Thornberry et al, 1997;Garcia-Calvo et al, 1999), but the autocatalytic cleavage site (PEPDA) in caspase-9 itself also exhibits poor similarity with the consensus sequence (Stennicke et al, 1999). Previous work has shown that Raf-1 contains an autoinhibitory domain within the first 330 amino acids of its N-terminus (Cutler et al, 1998;.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-9 cleaves Raf-1 at position D279, which is conserved in human and mouse Raf-1. D279 and its context do not fit the proposed consensus motif for a caspase-9 cleavage site (Thornberry et al, 1997;Garcia-Calvo et al, 1999), but the autocatalytic cleavage site (PEPDA) in caspase-9 itself also exhibits poor similarity with the consensus sequence (Stennicke et al, 1999). Previous work has shown that Raf-1 contains an autoinhibitory domain within the first 330 amino acids of its N-terminus (Cutler et al, 1998;.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other group III caspases, such as caspase-2 and -7, may be used with the present cleavage recognition site [17,18]. We note that other caspase proteins may be used as an alternative to caspase-3 if one determines that the aspartate in the P4 subsite (DXXD) results in a cleavage site in the target protein.…”
Section: Discussionmentioning
confidence: 99%
“…We note that other caspase proteins may be used as an alternative to caspase-3 if one determines that the aspartate in the P4 subsite (DXXD) results in a cleavage site in the target protein. For example, group II caspases, caspase-6, -8, -9, and -10 have a preference for branched apolar residues in the P4 position, whereas group I caspases, caspase-1, -4, and -5 have a preference for aromatic amino acids in the P4 position [17,18]. It is conceivable that mutations similar to those described here in procaspase-3 (D9A, D28A) may be made in any of the other 13 caspases, creating a myriad of protein purification systems that exploit the properties of caspase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This substrate is preferentially cleaved by caspase 3, and to a lesser extent by caspases 6, 7, 8, 9, and 10. 51 Accumulation of AMC fluorescence was monitored over 1 h using an HTS fluorescent plate reader (excitation 380 nm, emission 465 nm). Fluorescence of blanks containing no cell lysate was subtracted from the values.…”
Section: Measurement Of Caspase 3-like Protease Activitymentioning
confidence: 99%